Escrutinio de inhibidores de la aldosa reductasa en el exometaboloma de hongos endófitos de Cupressus sp. - Torres Villaseñor, Emmanuel (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
Diabetic cataract is closely associated with the polyol pathway. Aldose reductase (AKR1B1), an NADPH-dependent enzyme, catalyzes the reduction of glucose to sorbitol, an organic osmolyte. Under conditions of chronic hyperglycemia, AKR1B1 activity is upregulated, leading to oxidative stress. Sorbitol accumulation causes osmotic stress, and together these conditions contribute to the lysis of lens fiber cells; the aggregation of their remnants results in the formation of lens opacities known as diabetic cataracts. In the search for AKR1B1 inhibitors, evidence indicates that synthetic compounds such as epalrestat present toxicity issues and limited efficacy. Therefore, natural sources such as endophytic fungi represent a promising area of exploration. These organisms produce secondary metabolites with diverse biological activities, including the inhibition of oxidoreductase enzymes. In this study, AKR1B1 from rabbit lenses was analyzed. Its purification was optimized using dithiothreitol to preserve the enzyme's structural stability, and its sensitivity to dimethyl sulfoxide (DMSO) was assessed by determining concentrations that inhibit its activity. Fungal metabolites showed potential as enzyme inhibitors or activators. Among nine endophytic fungi isolated from Cupressus sp., some acted as AKR1B1 inhibitors, others as activators, while a group showed no significant effect. The exometabolome of the endophytic fungus Paraconiothyrium sp. exhibited the strongest inhibitory effect on AKR1B1. Metabolomic analyses identified a group of potential AKR1B1 inhibitors, including UMSNH-ETV21, which was isolated and shown to inhibit AKR1B1 through molecular docking and enzymatic kinetics assays.

La catarata diabética se relaciona estrechamente con la vía de los polioles, la aldosa reductasa (AKR1B1) dependiente del NADPH cataliza la transformación de glucosa a sorbitol el cual tiene una función de osmolito orgánico. En condiciones de hiperglucemia crónica la actividad de la AKR1B1 aumenta lo que induce al estrés oxidativo por agotamiento del NADPH, mientras que el sorbitol al acumularse provoca el estrés osmótico ambas condiciones conllevan a la lisis celular de las células que conforman al cristalino y la acumulación de ellas forma una opacidad que se conoce como catarata diabética. En la búsqueda de inhibidores de la AKR1B1, se tiene evidencia que los compuestos sintéticos como el epalrestat presentan problemas de toxicidad y baja eficacia, por lo que un área por explorar es a partir de fuentes naturales, como los hongos endófitos los cuales producen metabolitos secundarios con diversas funciones biológicas, entre ellas la inhibición de enzimas óxido-reductoras. Nueve hongos endófitos de Cupressus sp. mostraron efectos sobre la inhibición de la enzima AKR1B1. Siendo el exometaboloma del hongo endófito Paraconiothyrium sp. es el que presentó el mayor efecto inhibitorio sobre la AKR1B1, la identificación metabolómica de los potenciales inhibidores muestra al metabolito UMSNH-ETV21 con el mejor efecto inhibitorio sugiriendo su posible uso para tratar la catarata diabética mediante la reducción de la acumulación de sorbitol en el cristalino.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-R-M-2025-1445; Exometaboloma; Aldosa reductasa; Catara; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19452